Egg clutch structure of Rhinella rumbolli (Anura: Bufonidae), a toad from the Yungas of Argentina, with a review of the reproductive diversity in Rhinella - Pereyra, Martín Oscar (2015)
Rhinella rumbolli is a poorly known, medium-sized toad endemic to the Yungas of Argentina. Recent fieldwork allowed observing its peculiar oviposition mode, which is described in this paper. A review of literature and examination of museum material indicate that oviposition in Rhinella can vary from strings of eggs in a gelatinous tube (uniserial, biserial or multiserial) to open clumps. Clutch features in Rhinella provide informative variation for taxonomic and phylogenetic studies and help to understand the relationships in this large genus of true toads.